Konsep Al-Islam dalam Al-Qurâ€™an - Misbahuddin Jamal (Al-Ulum, 2011)
As a religion of revelation, Islam has a set of teachings contained the teachings of monotheism or the oneness of God. It also has systems and provisions that govern all human life. Allah states that Islam is a blessed religion. People who believe it will get salvation in the hereafter. And anyone denies it would be classified as the losers. Literally, Islam has several meanings, among others:â€œAl istislamâ€ (surrender), â€œAs Salamahâ€ (safety), â€œAs Salamâ€ (safe and prosperous), â€œAs Silmuâ€ (peace), and â€œSullamâ€ (saved). The Koran firmly stated that all religions revealed to the Prophets and Messengers before Muhammad was essentially Islam. Diverse manifestations, but the core of all the previous religions was the devotion to the One Being, namely God.